( 1 − x 3 2 ) ( 1 − x 1 + x + 1 1 + x 2 + 1 2 + 1 + x 4 4 + 1 + x 8 8 + 1 + x 1 6 1 6 ) = ?
This is part of the series: It's easy, believe me!
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
A lovely problem if you don't know the answer is a particular number. But, in the context of being asked for an answer we can type into the form, there is a cheat: let x = 0.
If we get a particular answer whatever the value of x, then any value will reveal that answer. 0 is the easiest to calculate. Of course, x can't be 1.
x can't be 1
Problem Loading...
Note Loading...
Set Loading...
X = ( 1 − x 3 2 ) ( 1 − x 1 + 1 + x 1 + 1 + x 2 2 + 1 + x 4 4 + 1 + x 8 8 + 1 + x 1 6 1 6 ) = ( 1 − x 3 2 ) ( ( 1 − x ) ( 1 + x ) 1 + x + 1 − x + 1 + x 2 2 + 1 + x 4 4 + 1 + x 8 8 + 1 + x 1 6 1 6 ) = ( 1 − x 3 2 ) ( 1 − x 2 2 + 1 + x 2 2 + 1 + x 4 4 + 1 + x 8 8 + 1 + x 1 6 1 6 ) = ( 1 − x 3 2 ) ( 1 − x 4 4 + 1 + x 4 4 + 1 + x 8 8 + 1 + x 1 6 1 6 ) = ( 1 − x 3 2 ) ( 1 − x 8 8 + 1 + x 8 8 + 1 + x 1 6 1 6 ) = ( 1 − x 3 2 ) ( 1 − x 1 6 1 6 + 1 + x 1 6 1 6 ) = ( 1 − x 3 2 ) ( 1 − x 3 2 3 2 ) = 3 2